THE DEVELOPMENT OF EFFECTIVENESS ASSESSMENT SYSTEM OF SCIENTIFIC-TEACHING STAFF BASED ON INTEGRATED INFORMATION-EDUCATIONAL ENVIRONMENT - Mikhail S. Gasparian (Открытое образование (Москва))
The article discusses the development of a comprehensive effectiveness assessment system of scientific-teaching staff of the university in the context of improving the quality of higher education. In this connection, an attempt has made to formulate a generalized model of evaluating the effectiveness of teachers by taking into account the various components of information-educational environment.